2017
DOI: 10.1055/s-0037-1598107
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Osteochondral Allografts: Can We Improve the Matching Process?

Abstract: An important consideration for the successful use of fresh osteochondral allografts for the patellofemoral joint is selection of appropriately sized donor allografts. This is particularly challenging for matching grafts to the patella because of the substantial variability in articular contour that exists. At present, selection of donor patellae is based only on the width of the proximal tibia, with no established means of quantifying basic patellar size, facet configuration, or articular contour. We hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…It is known that the patellar cartilage is thicker than that of the femoral condyles, and previous studies have shown that mismatch of host and graft height leads to significantly increased contact pressures. 6 , 13 However, in the case of nonorthotopic grafting, given different thicknesses of the cartilage layer, even if equal overall height is achieved, it is possible that a mismatch in subchondral plate congruity may lead to aberrant loading on the deep layer of the cartilage, which may portend poorer outcome. Further investigation is warranted to characterize the radiographic morphologic characteristics over time and elucidate the longevity of nonorthoptic patellar OCA using FCA donor in comparison with other cartilage regeneration techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the patellar cartilage is thicker than that of the femoral condyles, and previous studies have shown that mismatch of host and graft height leads to significantly increased contact pressures. 6 , 13 However, in the case of nonorthotopic grafting, given different thicknesses of the cartilage layer, even if equal overall height is achieved, it is possible that a mismatch in subchondral plate congruity may lead to aberrant loading on the deep layer of the cartilage, which may portend poorer outcome. Further investigation is warranted to characterize the radiographic morphologic characteristics over time and elucidate the longevity of nonorthoptic patellar OCA using FCA donor in comparison with other cartilage regeneration techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the bony shape, chondral thickness, and surface function (sliding articulation rather than rolling, which occurs in the condyles) are all distinct challenges to proper matching. 6 , 13 Ideally, transplant of an osteochondral allograft uses a donor graft that matches the morphologic features of the host joint architecture, although a slight mismatch has been shown to be acceptable, with unchanged clinical outcomes. 20 Condyle-specific matching, for instance, MFC graft for MFC lesion, was traditionally performed in an effort to minimize incongruity between graft and host.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The same principle applies to OCA, but the process of donor graft matching is complicated by the anatomic complexity and variability of the PFJ. Proper assessment of preoperative imaging studies for PFJ allograft matching is yet to be determined [ 83 , 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lattermann et al 14 recently stated how the anatomy and curvature of both the femoral trochlea and patellar facets make donor graft sizing and preparation exceedingly difficult, which may also influence outcomes. While exciting new research into improving the matching process for patellofemoral OCA grafts continues to be performed, 20 currently, graft matching and preparation can be quite challenging for surgeons using a plug technique to attain the curvature desired to restore smooth articulation.…”
Section: Discussionmentioning
confidence: 99%